Load flow analysis in IEEE 14 Bus system Using FACTS Device - Abdul Karim Barna, Harpreet Kaur, Sarbjeet Kaur (International Journal of Advanced Science and Technology, 2020)
The unify power flow regulator (UPFC) is a typical FACTS device which is the most useful power electronic equipment that has emerged to control and optimize the flow of power and even to adjust the voltage profile of transmission System. This paper proposes real control, reactive power and voltage across a transmission line, positioning the UPFC at the transmitting end using Power World simulator. Voltage stability refers to the ability of a power system to maintain acceptable voltages on all the underlying buses after being subjected to disturbances. The assessment of voltage stability has also become more complex due to the strengthening of power systems. The L index is the parameter used to verify stability .This paper focus on analyzing the performance of the IEEE-14 bus system for voltage stability, calculating the voltage drop point, and increasing the stability of the power system.